'If I do science, I can get the money': a life history analysis of postsecondary students' decisions to pursue teaching careers in STEM. (2nd January 2022) - Smith, Katie N.
ABSTRACT: The teaching profession is facing difficulty recruiting and retaining talent in the U.S., especially in STEM subjects. This study identifies the key experiences that shaped the academic paths and career plans of 10 pre-service teachers in STEM education who are participating in a loan forgiveness programme in North Carolina. Using life history methodology, category-centred analysis based on social cognitive career theory revealed six themes. Findings show the importance of early school experiences in inspiring interests in teaching, with participants also pursuing teaching-related roles to explore growing career interests. Participants tended to develop interests in STEM subjects separately from their interests in teaching, often as a result of academic success in STEM, especially when participants had good teachers in these subjects. However, participants were frequently dissuaded from pursuing teaching careers by family members and educators. The opportunity for loan forgiveness was a significant motivator for several participants to newly consider careers in STEM education, suggesting the salience of college costs and student debt in teacher recruitment efforts today.